O sentido do trabalho na contemporaneidade: um estudo de caso - Jardim, Fernanda Santana (2010)
This research entitled "The effect on labor: a case study," aims are to promote the approach of the reader of the issues surrounding the work today in the context of post-modernity, in the forms of management features of the new capitalism globalized world, presenting concepts of various authors on the subject, our own perceptions and the result of research on the subject. To do so, proceeded to a literature search / exploration on the topic in question. Then there was a case study, supplemented by a field survey of qualitative character. From the confrontation of the data submitted by the authors surveyed on issues related to work and observation in the environment studied, we could understand the importance to be given by all segments of society, including businesses and schools to: the concern with building a working model best suited to the holistic characteristics of the worker, respecting your physical, intellectual and psychological, while ensuring and enhancing human dignity, avoiding diseases such as stress, so common today and most of the time caused by man's distance from himself and his social group. The demands of contemporary work apart the man most of those realities that include the place and in a reality permeated with aggressive and strong demands of competitiveness that are striking features of the new models of management in a globalized world. The case study can be seen that management models are demanding, given the need to stay in the business market, also can be seen that the possibility of flexibility in the conduct of the many demands of work, by managers and or responsible for the administration still appears as a factor for minimizing the stress, but does not alter this reality. With regard to field research, research on the meaning of work in the lives of workers, shows that they attach great part of the meaning of his work for the maintenance of social status and belonging that the work gives them. This led us to intensify the belief that there is removal of the meaning of work and that this factor contributes increasingly to the development of diseases and empty. It is necessary that policies for managing contemporary enterprises prioritize and ensure through its internal policies, the holistic development of the worker, ensuring the possibility of synthesizing the size of their work to other parts of his life in an organized and healthy